Studi Pemberdayaan Masyarakat pada Program Dana Desa di Desa Pa’batangang, Kec. Mappakasunggu, Kab. Takalar - Zainal, Nining Haslinda; Elvira, Fivi; Jafar, Rizka (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
This article examines How the Design of the Society Empowerment Field Program, and the factors of resistor empowerment Field at Desa Pa’batangang, Kecamatan Mappakasunggu, Kabupaten Takalar. This phenomenon seeing that countryside fund policy is not maximum to superintendence it, by seeing of the indication of less involvement societies to the forum of countryside development plan, and the effects are many activities that unsuitable with society’s needs, and the execution of activity is not well presentation. In Permendesa PDTT number 11 years 2019 clause 5 concerning use priority countryside funds, it states that there are two sectors that become priority; countryside development and society empowerment which these two sectors should run simultaneously. However, Society Empowerment Field Program become neglected, most of the utilization countryside fund only focused on physical project, staff like pretend resources potency which is exist in countryside. Whereas, towards build the autonomous countryside, it very important to have support from government that become beneficial. This article may useful for the government of Takalar regency, along expansion countryside fund program. Research informant: Head of Countryside, Staff, Technical Practitioner, and Societies. Research scientific used qualitative. Data aggregation through interview, observation, secondary data study. Researcher used Data analysis technique’s Miles and Huberman. Based on research, that the result of Program manifested in two sectors; development and society empowerment. From both sectors, it shows that there is Fund Allocation distributed on activity which is not productive and there is no impact on society’s economic growth. Thereafter, which become resistor factor of the society empowerment are rigid regulation and the homogeneous activity, less manpower, less socialization, society access to the program is low and tend to hegemonic, the society only involved in taking and implementing activity, and the consequence is simply tend to active formality.